Slovenska antropologija v 21. stoletju - Naterer, Andrej (Traditiones (Ljubljana), 2022)
Starting with the question, “What is anthropology in Slovenia at the onset of the 21st century?,” we performed a content analysis of 1162 articles, book chapters, research reports, and books authored by Slovenian anthropologists between 2000 and 2021 and found several basic structures and themes that delineate a map of Slovenian anthropology. The results show that (1) within Slovenian anthropology there are 25 thematic groups that can be categorized as primary, secondary, and tertiary, based on their frequency and continuity; (2) Slovenian anthropology exhibits thematic variety, but its central themes are relatively isolated and narrow in focus; (3) the field of Slovenian anthropology is heavily feminized; (4) it exhibits low levels of international reach, making it primarily limited to national context; and (5) themes within Slovenian anthropology exhibit relatively low levels of scientific reach.
Keywords: 21. st.; 21st cent.; analize vsebine; content analyses; Slovenian anthropology; slovenska antropologija; tematske analize; thematic analyses